1966
DOI: 10.4153/cjm-1966-014-3
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of a Graph by Set Intersections

Abstract: Geometrically, a graph is a collection of points (or vertices) together with a set of edges (or curves) each of which joins two distinct vertices of the graph, and no two of which have points in common except possibly end points. Two given vertices of the graph may be joined by no edge or one edge, but may not be joined by more than one edge. From an abstract point of view, a graph G is a collection of elements ﹛x1, x2, …﹜ called points or vertices, together with a second collection of certain pairs (xα, Xβ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
198
0
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(200 citation statements)
references
References 2 publications
0
198
0
2
Order By: Relevance
“…In [2] it is shown that cc(D)-k2/4 for all k-vertex graphs D . Therefore the edges of H with both ends in U or both ends in V can be covered by at most IUJ 2 /4 or JV1 2/4 cliques respectively .…”
Section: Resultsmentioning
confidence: 99%
“…In [2] it is shown that cc(D)-k2/4 for all k-vertex graphs D . Therefore the edges of H with both ends in U or both ends in V can be covered by at most IUJ 2 /4 or JV1 2/4 cliques respectively .…”
Section: Resultsmentioning
confidence: 99%
“…They showed that φ(n, K 3 ) = ex(n, K 3 ), where ex(n, H) denotes the maximum size of a graph on n vertices, that does not contain H as a subgraph. Moreover, these authors proved in [5] that the only graph that maximizes this function is the complete balanced bipartite graph. Consequently, they conjectured that φ(n, K r ) = ex(n, K r ) and the only optimal graph is the Turán graph T r−1 (n), the complete balanced (r − 1)-partite graph on n vertices, where the sizes of the partite sets differ from each other by at most one.…”
Section: Introduction and New Resultsmentioning
confidence: 99%
“…This function was studied first by Erdős, Goodman and Pósa [5], who were motivated by the problem of representing graphs by set intersections. They showed that φ(n, K 3 ) = ex(n, K 3 ), where ex(n, H) denotes the maximum size of a graph on n vertices, that does not contain H as a subgraph.…”
Section: Introduction and New Resultsmentioning
confidence: 99%
“…-A classical result of Erdős, Goodman and Pósa [16] states that Θ 1 (G) ≤ Θ 1 (K n,n ) = n 2 for every graph G on 2n vertices, where K n,n is a complete bipartite n × n graph. Moreover, a desired covering of G can be achieved by only using simplest complete subgraphs: edges and triangles.…”
Section: Known Resultsmentioning
confidence: 99%